2019
DOI: 10.1016/j.joms.2018.06.173
|View full text |Cite
|
Sign up to set email alerts
|

Maxillomandibular Advancement Improves Multiple Health-Related and Functional Outcomes in Patients With Obstructive Sleep Apnea: A Multicenter Study

Abstract: MMA is a highly effective and safe treatment for OSA, which predictably leads to significant improvements in sleepiness, QOL, sleep-disordered breathing, and neurocognitive performance, as well as a reduction in cardiovascular risk (blood pressure).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
45
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(68 citation statements)
references
References 54 publications
7
45
1
3
Order By: Relevance
“…51 Recently, a prospective multicenter study which evaluated the success of MMA for OSA reported significant improvements in mean ESS (13.3 to 4.9) and AHI (39.6 to 7.9) values. 52 These results are consistent with the 2016 meta-analysis by Zaghi et al, which documented 98.8% improvement in AHI and RDI values after MMA, based on 45 studies with a total of 518 unique cases. 53 Every surgery carries risks and potential complications, likewise MMA is an invasive surgery that could cause numbness, pain and swelling around the maxillofacial region.…”
Section: Maxillomandibular Advancementsupporting
confidence: 89%
“…51 Recently, a prospective multicenter study which evaluated the success of MMA for OSA reported significant improvements in mean ESS (13.3 to 4.9) and AHI (39.6 to 7.9) values. 52 These results are consistent with the 2016 meta-analysis by Zaghi et al, which documented 98.8% improvement in AHI and RDI values after MMA, based on 45 studies with a total of 518 unique cases. 53 Every surgery carries risks and potential complications, likewise MMA is an invasive surgery that could cause numbness, pain and swelling around the maxillofacial region.…”
Section: Maxillomandibular Advancementsupporting
confidence: 89%
“…Among the studies, 31 were published as full‐text articles and were thus assessed in this meta‐analysis. Eleven studies described adults with OSA who received surgery and provided CRP measurements 23–33 . However, two studies by Marvisi et al and Vicente et al did not provide raw data required for meta‐analysis 23,24 ; their corresponding authors were contacted, but the data were still unavailable.…”
Section: Resultsmentioning
confidence: 99%
“…127 Another example from a study of maxillomandibular advancement surgery showed a similar improvement in the total FOSQ score, with an increase from a mean score of 14.1 to 18.3. 138 In addition, a study on hypoglossal nerve stimulation with 126 patients found an improvement in total FOSQ score from 14.3 to 17.3. 103 By contrast, an RCT conducted by Marklund et al found no significant differences at follow-up in total FOSQ score or KSQ between MRD and a placebo device, though PSG improved.…”
Section: Study III -Sleep Quality After Uvulopalato-pharyngoplastymentioning
confidence: 99%